Analysis of Fundamental Factors Affecting Company Financial Performance (Study on the Sector Automotive on the Indonesia Stock Exchange) - Karyawati, Endang (CV. Satria Jaya, 2025)
Company fundamental factors is one of the factor important for increase performance finance company in the future future. Research This aim For analyze characteristics company to capital structure, influence capital structure against performance finance, Data analysis methods used in study This using a path analysis model and data processing using the WarpPLS (Partial Least Square ) program . Research use sample company automotive companies listed on the Indonesian Stock Exchange. Research produce, (1) Characteristics company influential significant to capital structure; (2) Characteristics company influential significant to performance finance (3) Capital structure has an effect significant on financial performance. Conclusion.Findings study improvement characteristics company own influence to the company's capital structure is characterized by improvement improvement use high capital structure. Increase characteristics high-ranking companies, which are characterized by decrease in return of investment (ROI). Changes Company characteristics and capital structure have an influence to performance finance company